Understanding Tourist Preferences for Sustainable Tourism Practice in Central Europe - Wicaksono, Tutur; Marhadi (Journal of Tourism and Economic, 2024)
This study examines how tourists prioritize sustainable practices in Central Europe using the Kano model. With the growing importance of sustainability in tourism, there is limited research on how tourists evaluate different sustainable practices in this region. The objectives are to classify sustainable tourism practices into five Kano quality categories based on tourist preferences and to identify the key practices tourists prioritize when selecting destinations. A quantitative approach was used, surveying 250 tourists in Budapest, who rated 12 sustainable tourism practices. The data were analysed to categorize these practices as "Must-be," "One-dimensional," "Attractive," "Indifferent," or "Reverse." The results revealed that environmental conservation (M = 84.4%), wildlife-friendly tourism (M = 77.6%), and waste reduction (M = 75.2%) were the top priorities, classified as "Must-be" attributes, indicating their essential role in tourist satisfaction. In contrast, fair trade practices (68.8%) received lower priority. These findings suggest that tourists in Central Europe place more value on visible environmental sustainability efforts rather than ethical practices like fair trade. The study highlights the importance of focusing on environmental conservation, wildlife protection, and waste reduction in tourism strategies. By understanding these preferences, tourism stakeholders can develop strategies that align with tourists' priorities, supporting both sustainability and economic growth in the region.